Molecular engineering strategies for fabricating efficient porphyrin-based dye-sensitized solar cells. Issue 6 (6th April 2020) - Zeng, Kaiwen; Tong, Zhangfa; Ma, Lin; Zhu, Wei-Hong; Wu, Wenjun; Xie, Yongshu
Abstract : In this review, intra- and intermolecular engineering strategies for improving the efficiencies of porphyrin based dye-sensitized solar cells are briefly summarized, revealing the in-depth structure–photovoltaic performance correlations. Abstract : Dye-sensitized solar cells (DSSCs), as a cost effective and eco-friendly photovoltaic technology for utilizing solar energy, are promising in meeting the increasing demand of clean and renewable energy resources. Among various sensitizers, porphyrins are crucial candidates with the advantages of strong absorption in a wide spectral range, tunable photophysical and electrochemical properties, and long-lived excited states facilitating electron injection. After decades of development, the power conversion efficiencies of porphyrin-based DSSCs have exceeded 13%, showing the great potential of porphyrins in fabricating highly efficient DSSCs. This review summarizes effective molecular engineering strategies for optimizing porphyrin sensitizers as well as intermolecular engineering of coadsorption and cosensitization systems, with the aim to provide further insight into the molecular structure–photovoltaic performance correlations and an outlook on possible exploration directions in the future for achieving DSSCs with high efficiencies, long-term stability and low cost feasible for practical applications. In addition, the recent advances of porphyrin-based organic solar cells (OSCs) are briefly introduced considering similar design strategies employed for developing porphyrin dyes for DSSCs and active materials for OSCs.